Exploring the implications of distinct mutational signatures and mutation rates in aging and cancer. Issue 1 (December 2016) - Fox, Edward; Salk, Jesse; Loeb, Lawrence
Editorial summary Signatures of mutagenesis provide a powerful tool for dissecting the role of somatic mutations in both normal and pathological processes. Significantly, cancer genomes are dominated by mutation signatures distinct from those that accumulate in normal tissues with age, with potentially important translational implications.